An exploration of factors that help or hinder the successful learning of the English Language among secondary school students - Syed Mohamed Abdul Gaffoor. (2008)
This is a qualitative study of some of the factors that may help or hinder the successful learning of the English Language among secondary school students in the express stream. It attempts to establish through the subjects' responses and perceptions whether these factors help or hinder the learning of English successfully.